Conflictos entre poblaciones autóctonas y las industrias extractivas: Perú y los andes frente a los desafios del siglo XXI - Noejovich, Héctor Omar (2016)
This paper aims to an historical review of the State and native population relationship from Spanish intrusion to the present throughout the cultural shock and legislation.